2024
DOI: 10.3390/v16020217
|View full text |Cite
|
Sign up to set email alerts
|

Sotrovimab: A Review of Its Efficacy against SARS-CoV-2 Variants

Daniele Focosi,
Arturo Casadevall,
Massimo Franchini
et al.

Abstract: Among the anti-Spike monoclonal antibodies (mAbs), the S-309 derivative sotrovimab was the most successful in having the longest temporal window of clinical use, showing a high degree of resiliency to SARS-CoV-2 evolution interrupted only by the appearance of the BA.2.86* variant of interest (VOI). This success undoubtedly reflects rational selection to target a highly conserved epitope in coronavirus Spike proteins. We review here the efficacy of sotrovimab against different SARS-CoV-2 variants in outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated an excellent clinical response in immunocompromised patients with prolonged COVID-19 by combining two antivirals (mainly remdesivir and nirmatrelvir/ritonavir) with mAbs [287]. Thus, employing a blend of mAbs alongside concurrent small-molecule antiviral treatments, such as protease and replicase inhibitors, can mitigate the risk of resistance emergence, ensuring more robust and lasting efficacy against evolving viral strains [146,288]. However, the elevated risks associated with safety concerns, potential drug interactions, and adverse effects of these therapies may account for a portion of the limited number of subjects undergoing clinical trials for COVID-19 at this time.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…A recent study demonstrated an excellent clinical response in immunocompromised patients with prolonged COVID-19 by combining two antivirals (mainly remdesivir and nirmatrelvir/ritonavir) with mAbs [287]. Thus, employing a blend of mAbs alongside concurrent small-molecule antiviral treatments, such as protease and replicase inhibitors, can mitigate the risk of resistance emergence, ensuring more robust and lasting efficacy against evolving viral strains [146,288]. However, the elevated risks associated with safety concerns, potential drug interactions, and adverse effects of these therapies may account for a portion of the limited number of subjects undergoing clinical trials for COVID-19 at this time.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%